Pulsed Laser Beam Welding of Pd43Cu27Ni10P20 Bulk Metallic Glass - Ling Shao (Nature Portfolio, 2017)
Abstract We used pulsed laser beam welding method to join Pd43Cu27Ni10P20 (at.%) bulk metallic glass and characterized the properties of the joint. Fusion zone and heat-affected zone in the weld joint can be maintained completely amorphous as confirmed by X-ray diffraction and differential scanning calorimetry. No visible defects were observed in the weld joint. Nanoindentation and bend tests were carried out to determine the mechanical properties of the weld joint. Fusion zone and heat-affected zone exhibit very similar elastic moduli and hardness when compared to the base material, and the weld joint shows high ductility in bending which is accomplished through the operation of multiple shear bands. Our results reveal that pulsed laser beam welding under appropriate processing parameters provides a practical viable method to join bulk metallic glasses.